4-Phenylbutyric acid improves free fatty acid-induced hepatic insulin resistance in vivo. Issue 8 (28th July 2021) - Pereira, Sandra; Moore, Jessy; Li, Jia-Xu; Yu, Wen Qin; Ghanim, Husam; Vlavcheski, Filip; Joseph, Yemisi Deborah; Dandona, Paresh; Volchuk, Allen; Cummins, Carolyn L; Tsiani, Evangelia; Giacca, Adria
Abstract : Plasma free fatty acids (FFAs) are elevated in obesity and can induce insulin resistance via endoplasmic reticulum (ER) stress. However, it is unknown whether hepatic insulin resistance caused by the elevation of plasma FFAs is alleviated by chemical chaperones. Rats received one of the following i.v. treatments for 48 h: saline, intralipid plus heparin (IH), IH plus the chemical chaperone 4-phenylbutyric acid (PBA), or PBA alone and a hyperinsulinemic-euglycemic clamp was performed during the last 2 h. PBA co-infusion normalized IH-induced peripheral insulin resistance, similar to our previous findings with an antioxidant and an IκBα kinase β (IKKβ) inhibitor. Different from our previous results with the antioxidant and IKKβ inhibitor, PBA also improved IH-induced hepatic insulin resistance in parallel with activation of Akt. Unexpectedly, IH did not induce markers of ER stress in the liver, but PBA prevented IH-induced elevation of phosphorylated eukaryotic initiation factor-2α protein in adipose tissue. PBA tended to decrease circulating fetuin-A and significantly increased circulating fibroblast growth factor 21 (FGF21) without affecting markers of activation of hepatic protein kinase C-δ or p38 mitogen-activated protein kinase that we have previously involved in hepatic insulin resistance in this model. In conclusion: (i) PBA prevented hepatic insulin resistance caused by prolonged plasma FFA elevation without affecting hepatic ER stress markers; (ii) the PBA effect is likely due to increased FGF21 and/or decreased fetuin-A, which directly signal to upregulate Akt activation.